A typology of food security in developing countries - Yu, Bingxin; You, Liangzhi (Emerald Publishing Limited, 2013)
The recent high food price and volatility, as well as economic recession, have reversed the last decade's progress in reducing hunger and poverty. This aim of this paper is to conduct a factor and sequential typology analysis to identify groups of countries categorized according to five measures of food security.The recent high food price and volatility, as well as economic recession, have reversed the last decade's progress in reducing hunger and poverty. This paper conducts a factor and sequential typology analysis to identify groups of countries categorized according to five measures of food security – consumption, production, imports, distribution, and agricultural potential – by using indicators from 175 countries. The analysis first identifies five distinct food security groups, measured by the levels of nutrient intake, and then further splits these groups based on indicators of food production, trade security, and agricultural potential.The results suggest that the terms of “developing country” or “low income country” can be inaccurate in the discussion of food security because they are too general and can actually mask the extreme heterogeneity in different aspects of food security. The results also indicate that different responses are needed by different types of food‐insecure countries to address their unique food and economic challenges.The typology of food security and linkage between agricultural potential and food security contribute to a better understanding of the effectiveness of different policy interventions under a country's unique conditions.